A contrastive study of quantifiers in English and in Vietnamese / Vu Thanh Binh, Supervisor: Dr. Dang Ngoc Huong - Vu, Thanh Binh
The title of my thesis is a study on A contrastive study of Quantifiers in English and in Vietnamese. The reason that I choose this thesis is Through the process of teaching English in mountainous areas to ethnic minority students, I see that students in mountainous areas in general and ethnic minority students in particular have many difficulties in using words in English, especially using the right kind of words, stemming from that fact, I decided to do this topic to better understand quantifiers and word denoting quality in order to better understand this field and help students in upland areas understand and understand and use them correctly. The purpose of my study is to describe the semantic and syntactic features of Quantifiers in English and in Vietnamese, and propose the implications for teaching these ones at high school. To carry out this research, I use descriptive, analytical and contrastive method. Hopefully, the finding of this study can, to some extent, be suggested as a referential materials for Vietnamese students and teachers in studying and teaching quantifiers. Finding the correct use of Word denoting quality has important implications for ethnic minorities in using correct words in English.